DAMPAK MEDIA TERHADAP ASUMSI MASYARAKAT STUDI KASUS GOLONGAN BA’ALAWI DI INDONESIA - Arista, Riky (Al-Amien Prenduan University, Sumenep, 2025)
This research discusses the dynamics of public perception towards the Ba'alawi group in Indonesia in the context of social media development and changes in the paradigm of religious authority. The Ba'alawi group claims direct descent from the Prophet Muhammad through a lineage connected to Ahmad al-Muhajir. This claim has been accepted for centuries with little challenge; however, it now faces serious challenges, particularly in the digital age. Social media platforms such as TikTok, YouTube, and Instagram have become open spaces for the public to question the validity of the lineage, the style of preaching, and the symbolic authority of this group. The research employs a qualitative approach with techniques including observation, interviews, and documentation to provide an in-depth description of the public's response to this issue. The findings indicate a shift from traditional reverence towards critical evaluation based on academic assessments and empirical evidence, such as DNA testing and historical studies. Polarization has emerged from various groups, including pesantren, academics, and the younger generation, which exhibit more moderate and rational attitudes. Furthermore, the conflict surrounding Ba'alawi is not solely theological but is also closely linked to social-political dynamics and the struggle for authority within contemporary Muslim society. This research emphasizes the importance of digital literacy, inclusive preaching, and a scientific dialogical approach to alleviate tension and maintain social cohesion. In conclusion, social media plays a significant role in reshaping public perceptions of religious authority and Ba'alawi lineage, as well as being a key factor in the transformation of religious identity in the era of globalization.